Menstrual poverty: a systematic review to identify vulnerable populations and measurement tools - Nascimento, Maria Isabel do; Costa, Ana Luiza Morgado; Silva, Gabriella Lima Pereira da; Jesus, Katherine da Silva de; Lemes, Maria Clara de Oliveira; Maia, Paula Barbosa (O Mundo da Saúde, 2024)
The objective was to present a synthesis of the literature on the topic ‘menstrual poverty’. The search considered the sources PubMed/MEDLINE, LILACS, SCIELO Brazil and Google Scholar site. Pairs of researchers conducted the review steps according to the PRISMA guidelines, and assessed the quality of the evidence using the Mixed Methods Appraisal Tool. A total of 2,457 publications were identified, and 22 of them were included in the review. The concept outlined from this review suggests that “menstrual poverty corresponds to a multidimensional condition symbolically materialized by the lack of genital care products, which expresses, above all, the psychosocial vulnerability of the person who menstruates caused by the deprivation of the right to fundamental goods necessary for the enjoyment of a dignified and respectful life”. Age and socioeconomic conditions are the main markers of vulnerability to ‘period poverty’. A vast list of questions delves into the subject, primarily exploring aspects such as access, affordability, and availability of hygiene products to use during the menstrual flow period. By synthesizing the concepts and findings provided by the studies included in this review, it was possible to verify that the unfavorable socioeconomic factors are the most important makers of menstrual poverty. Although the menstrual poverty phenomenon is manifestation of essential goods deprivation and lack of human dignity, the research instruments and the solutions focused on access and supply of hygiene products. This reduction gives little visibility to the inequalities and social injustice that underlie the phenomenon of menstrual poverty.